A Construct Validity on Islamic Religiosity Scale: A Study on Indonesian and Malaysian Students - Tri Na’imah; Septiningsih, Dyah Siti; Suwarti; Panatik, Siti Aisyah (Technium Social Sciences Journal, 2021)
Several researchers have developed a tool to measure religiosity. Meanwhile, this study examined the validity of the construct of religiosity scale in the Islam context. The researcher named the Islamic religiosity scale to measure the religiosity of Islamic students in Indonesia and Malaysia. The data were collected from 511 Islamic students in Banyumas Regency, Indonesia, and Johor Bahru Malaysia. Then, the data were analysed through Structural Equation Modeling (SEM) SmartPLS 3.2.8. The analysis results proved that eight indicators were invalid, so they were eliminated from this scale. The remaining 17 indicators were unidimensional and measured the Islamic religiosity construct. Keywords: Construct Validity, Islamic religiosity, students